Nitrogen-doped alloy catalyst as well as preparation method and application thereof
Through the preparation method of nitrogen-doped alloy catalyst, the problems of high cost and insufficient performance of existing fuel cell catalysts are solved, and the effects of high catalytic activity and durability are achieved, and the overall cost of fuel cells are reduced.
Patent Information
- Application Number
- CN202510022685.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-03-21
AI Technical Summary
The oxygen reduction reaction catalysts in existing proton exchange membrane fuel cells are costly and have insufficient performance, especially the scarcity of precious metal resources and the durability of catalysts.
A nitrogen-doped alloy catalyst with high catalytic activity and durability is prepared by mixing a nitrogen precursor and a carbon support, heat treatment, mixing and reducing reaction of precious metals and rare earth elements.
The catalytic activity and kinetic properties of nitrogen-doped alloy catalysts in oxygen reduction reaction are significantly improved, the service life of the catalyst is extended, and the cost of fuel cells is reduced.
Smart Images

Figure CN119674111A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a nitrogen-doped alloy catalyst and a preparation method and application thereof. Background Art
[0002] As a clean and efficient energy conversion device, proton exchange membrane fuel cells (PEMFCs) have shown broad application prospects in transportation, distributed power generation and other fields in recent years. However, the commercialization of PEMFCs is limited by the cost and performance of its key material, the oxygen reduction reaction (ORR) catalyst. Currently, commercial ORR catalysts are mainly based on precious metal materials (e.g., platinum (Pt)), but precious metal resources are scarce, expensive, and there is a problem of insufficient catalyst durability. Therefore, how to develop low-cost, high-performance ORR catalysts is an important research direction in the field of PEMFCs.
[0003] In recent years, technicians in this field have been committed to reducing the amount of platinum through alloying, carrier modification and other means, while improving the activity and durability of the catalyst. Among them, low-platinum catalysts and rare earth element modified catalysts have become hot topics in this field. Rare earth elements have shown potential application value in ORR catalysts due to their unique electronic structure and catalytic properties.
[0004] CN118825307A discloses a method for preparing a rare earth element doped carbon nitride loaded noble metal electrocatalyst. The preparation method is based on rare earth element doped carbon nitride, loaded with noble metal-based nanoparticles, clusters or single atoms. The noble metal-based nanoparticles of the prepared electrocatalyst are evenly distributed and stable on the rare earth element doped carbon nitride carrier, and the interface bonding strength between the noble metal and the rare earth element doped carbon nitride carrier is greatly improved, so that the noble metal-based nanoparticles, clusters or single atoms can effectively maintain structural stability during the electrochemical reaction of the fuel cell cathode. However, the method is to use rare earth element doped carbon nitride as a carrier to load noble metals, and the amount of noble metals is still high, and rare earth elements are used as carrier components, and the effect of the precious metals is limited.
[0005] CN116053487A discloses a method for preparing a platinum-rare earth alloy catalyst. The preparation method comprises the following steps: 1) mixing g-C3N4, a platinum precursor, a rare earth precursor and a carbon carrier to obtain a mixture; 2) heating and reducing the mixture obtained in step 1) to obtain a reduction product; 3) acid-washing and etching the reduction product obtained in step 2) to obtain the platinum-rare earth alloy catalyst. The preparation method introduces g-C3N4 and uses the abundant nitrogen defect sites in its CN network structure to anchor platinum and rare earth ions, thereby obtaining a nano-scale highly dispersed catalyst under relatively mild conditions with oxygen and water. The method requires acid washing and etching of the obtained reduction product.
[0006] CN116845255A discloses a method for preparing various platinum-iron-rare earth alloys in situ at the gram level using a carbon carrier. The method comprises the following steps: S1, adding precursors of platinum, iron and rare earth elements and a catalyst carrier to a reaction vessel containing an alcohol solvent; S2, ultrasonically homogenizing the above mixture in an ultrasonic instrument; S3, placing the reaction vessel open, turning on magnetic stirring, placing it in an oil bath, and heating it at a certain temperature until it evaporates; S4, scraping the evaporated product with a scraper, and further transferring it to a mortar for grinding; S5, calcining the ground mixture in an argon-hydrogen mixed atmosphere at a certain temperature, and obtaining the final supported platinum-iron-rare earth alloy nanocatalyst after cooling. The catalyst prepared by this method is based on platinum-iron alloy as the catalyst body.
[0007] CN116463666A discloses a method for preparing a noble metal-rare earth alloy nanocluster catalyst. The method comprises: mixing and calcining a carbon material, a nitrogen source and a phosphorus source by ball milling to obtain a nitrogen-phosphorus functionalized activated carbon carrier; mixing and stirring the nitrogen-phosphorus functionalized activated carbon carrier with water and a rare earth salt, drying the obtained solid and then calcining it at high temperature to obtain a composite carrier; mixing and stirring the composite carrier with water and a noble metal salt, drying the obtained solid and then performing reduction calcination to obtain a noble metal-rare earth alloy nanocluster catalyst. The noble metal-rare earth alloy nanocluster catalyst prepared by the method is a catalyst with nitrogen-phosphorus functionalized activated carbon as a carrier. Summary of the invention
[0008] In view of this, one object of the present invention is to provide a method for preparing a nitrogen-doped alloy catalyst, wherein the obtained catalyst has good catalytic activity, catalytic kinetic performance and durability. Another object of the present invention is to provide a nitrogen-doped alloy catalyst obtained by the above preparation method. Another object of the present invention is to provide a use of the above nitrogen-doped alloy catalyst.
[0009] The present invention adopts the following technical solutions to achieve the above-mentioned purpose.
[0010] In one aspect, the present invention provides a method for preparing a nitrogen-doped alloy catalyst, comprising the following steps:
[0011] 1) dissolving a nitrogen precursor in a C2-C5 alkanediol to prepare a nitrogen precursor solution; adding a carbon carrier to the nitrogen precursor solution and mixing to obtain a mixed solution; wherein the mass ratio of the nitrogen precursor to the carbon carrier is 1:1-10;
[0012] 2) concentrating the mixed solution obtained in step 1) to obtain a concentrated product; drying the concentrated product to obtain a dried product;
[0013] 3) heat treating the dried product obtained in step 2) under protective gas at 200-1200° C. to obtain a nitrogen-doped carbon support;
[0014] 4) mixing the nitrogen-doped carbon carrier obtained in step 3) with an alkanediol solution of a noble metal salt and a solution of a rare earth element salt under the conditions of neutralization of C2-C5 alkanediol and protective gas to obtain a mixed solution; and adjusting the pH value of the mixed solution to 8-12; wherein the mass ratio of the salt of the rare earth element to the salt of the noble metal is 1:1-10; and the rare earth element is selected from at least one of neodymium, lanthanum, cerium, praseodymium, terbium, and dysprosium;
[0015] 5) The mixed solution after adjusting the pH value in step 4) is mixed with a solution of a reducing agent under protective gas and 40-120° C. and reacted to obtain a nitrogen-doped alloy catalyst.
[0016] According to the preparation method of the present invention, preferably, the solvents used in the solution of the noble metal salt, the solution of the rare earth element salt, and the solution of the reducing agent are C2-C5 alkanediols, respectively. Further preferably, the C2-C5 alkanediols are C2-C4 alkanediols.
[0017] According to the preparation method of the present invention, preferably, in step 1), the nitrogen precursor is selected from at least one of urea, ethylenediamine, benzylamine, melamine, pyrazine, polyacrylonitrile and polypyrrole. The carbon carrier is selected from at least one of carbon black, carbon nanotubes, mesoporous carbon and graphene.
[0018] According to the preparation method of the present invention, preferably, in step 2), the concentration temperature is 50-100° C., and the concentration time is 6-24 hours;
[0019] The drying temperature is 30-90° C., and the drying time is 1-12 hours.
[0020] According to the preparation method of the present invention, preferably, in step 4), the noble metal is selected from at least one of platinum, rhodium, palladium and iridium;
[0021] The salt of the noble metal is selected from at least one of a halogenated noble metal acid and a halogenated noble metal acid salt of an alkali metal;
[0022] In step 4), the salt of the rare earth element is selected from at least one of the halides of the rare earth element.
[0023] According to the preparation method of the present invention, preferably, in step 4), a C2-C5 alkanediol solution of an alkali metal hydroxide is used to adjust the pH value of the mixed solution.
[0024] According to the preparation method of the present invention, preferably, in step 5), the reducing agent is selected from at least one of alkali metal borohydride, sodium D-isoascorbate, catechol, ferrous sulfate, and stannous chloride.
[0025] According to the preparation method of the present invention, preferably, the protective gas is selected from at least one of nitrogen and inert gas.
[0026] On the other hand, the present invention also provides a nitrogen-doped alloy catalyst prepared by any of the above preparation methods. The nitrogen-doped alloy catalyst has a pore size of at least 9 nm and a pore volume of at most 0.37 cm 3 ·g -1 , the precious metal loading is at least 11 μg cm -2 .
[0027] In another aspect, the present invention also provides the use of the nitrogen-doped alloy catalyst in a proton exchange membrane fuel cell. The nitrogen-doped alloy catalyst as a cathode catalyst has a half-wave potential of at least 0.91 V in the oxygen reduction reaction and a Tafel slope of at most 40 mV·dec. -1 .
[0028] The nitrogen-doped alloy catalyst of the present invention has excellent catalytic activity, catalytic kinetic performance and durability in oxygen reduction reaction, and can significantly improve the performance of proton exchange membrane fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 TEM image of the nitrogen-doped alloy catalyst (Pt-Nd@HCN-400) prepared in Example 1.
[0030] Figure 2 TEM image of the nitrogen-doped alloy catalyst (Pt-Sm@HCN-400) prepared in Comparative Example 1.
[0031] Figure 3 TEM image of the alloy catalyst (Pt-Nd@HC-400) prepared in Comparative Example 2.
[0032] Figure 4 This is the BET calculation result diagram in Experimental Example 1.
[0033] Figure 5 This is the nitrogen absorption and denitrification curve diagram in Experimental Example 1.
[0034] Figure 6 This is the PXRD pattern in Example 2.
[0035] Figure 7 This is the LSV curve of Pt-Nd@HCN-400 in Experimental Example 4.
[0036] Figure 8 This is the LSV curve of Pt-Nd@HC-400 in Experimental Example 4.
[0037] Fig. 9 This is the LSV curve of Pt / C in Experimental Example 4.
[0038] Fig.10 This is the Tafel slope diagram in Experimental Example 4. DETAILED DESCRIPTION
[0039] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto.
[0040] The "half-wave potential" mentioned in the present invention refers to the potential when the current is equal to half of the diffusion current, usually denoted as E 1 / 2 , with the unit of V (volt), is used to measure the catalytic activity of the catalyst in the oxygen reduction reaction.
[0041] The "Tafel slope" mentioned in the present invention is also called Tafel slope, which refers to the slope of the straight line segment on the semi-logarithmic curve obtained by plotting the potential against the logarithmic value of the current density, and the unit is mV·dec -1 , which is used to measure the catalytic kinetic performance of a catalyst in the oxygen reduction reaction.
[0042] <Method for preparing nitrogen-doped alloy catalyst>
[0043] The preparation method of the nitrogen-doped alloy catalyst of the present invention comprises a step of mixing a nitrogen precursor with a carbon carrier, a step of concentrating and drying, a step of heat treatment, a step of mixing a noble metal with a rare earth element, and a step of reduction reaction, which is described in detail below.
[0044] Nitrogen precursor and carbon support mixing steps
[0045] A nitrogen precursor is dissolved in C2-C5 alkanediol to prepare a nitrogen precursor solution; a carbon carrier is added into the nitrogen precursor solution and mixed to obtain a mixed solution.
[0046] According to one embodiment of the present invention, the mass ratio of the nitrogen precursor to the carbon carrier may be 1:1-10, preferably 1:2-8, and more preferably 1:2-5.
[0047] According to one embodiment of the present invention, the nitrogen precursor can be selected from at least one of urea, ethylenediamine, benzylamine, melamine, pyrazine, polyacrylonitrile, and polypyrrole, preferably at least one of urea, ethylenediamine, benzylamine, melamine, and pyrazine, and more preferably at least one of urea, ethylenediamine, benzylamine, and melamine.
[0048] According to one embodiment of the present invention, the carbon carrier can be selected from at least one of carbon black, carbon nanotubes, mesoporous carbon, and graphene, preferably at least one of carbon black, carbon nanotubes, and mesoporous carbon, and more preferably carbon black or carbon nanotubes. The carbon carrier used in the present invention can use commercially available products. For example, according to a preferred embodiment of the present invention, the carbon black can be, but is not limited to, selected from at least one of Vulcan XC-72, Black Pearls 2000, and Ketjenblack EC-300J.
[0049] According to a specific embodiment of the present invention, the mixed solution can be mixed uniformly by stirring. The stirring method can use any stirring method known in the art, which is not particularly limited here. For example, but not limited to, a stirrer or ultrasound. The stirring time is based on the stirring uniformity, which is not particularly limited here. For example, but not limited to, it can be 10 to 120 minutes, preferably 10 to 100 minutes, and more preferably 20 to 90 minutes.
[0050] In the present invention, the C2-C5 alkanediol may be a C2-C4 alkanediol, preferably at least one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and 1,4-butanediol, and more preferably at least one of ethylene glycol, 1,2-propylene glycol, and 1,4-butanediol.
[0051] In the present invention, based on 1 mg of the nitrogen precursor, the amount of C2-C5 alkanediol used can be 0.2-5 mL, preferably 0.3-5 mL, and more preferably 0.5-4 mL.
[0052] In the present invention, when preparing a nitrogen-doped carbon carrier, a nitrogen precursor is used as a nitrogen source. When the nitrogen precursor is mixed with C2-C5 alkanediol and subjected to subsequent heat treatment, urea will decompose and release nitrogen elements, and the nitrogen elements are doped into the carbon carrier to form a nitrogen-doped carbon carrier. Nitrogen doping increases the defect degree and nitrogen content of the carbon carrier, thereby improving the anchoring ability and electronic regulation ability of the carbon carrier for metal nanoparticles, improving the electronic properties and surface properties of the carbon carrier, and improving the performance of the carbon carrier as a catalyst carrier.
[0053] The C2-C5 alkanediol of the present invention can be used as a solvent to help the nitrogen precursor and the carbon carrier to mix evenly. The C2-C5 alkanediol can also be used as an auxiliary agent for the reducing agent, and in the subsequent reduction reaction step, participates in the reaction of the noble metal element and the rare earth element, and helps the reducing agent to reduce the metal ions to metal elements. In addition, the C2-C5 alkanediol also participates in the nitrogen doping process of the carbon carrier, and promotes the doping of the nitrogen element through interaction with the nitrogen precursor.
[0054] The carbon carrier of the present invention can provide a large specific surface area and a rich pore structure as a catalyst support material, which is conducive to the dispersion and stability of metal particles. At the same time, the nitrogen-doped carbon carrier can also interact with the metal particles to further improve the performance of the catalyst.
[0055] Concentration and drying steps
[0056] The mixed solution is concentrated to obtain a concentrated product; the concentrated product is dried to obtain a dried product.
[0057] According to one embodiment of the present invention, the concentration temperature may be 50 to 100°C, preferably 55 to 95°C, and more preferably 60 to 90°C.
[0058] According to another embodiment of the present invention, the concentration time may be 6 to 24 hours, preferably 8 to 20 hours, and more preferably 10 to 18 hours.
[0059] In the present invention, the concentration can be achieved by any evaporation method or evaporation instrument known in the art, and is not particularly limited here, such as, but not limited to, using a rotary evaporator for rotary evaporation concentration.
[0060] According to one embodiment of the present invention, the drying temperature may be 30 to 90°C, preferably 40 to 80°C, and more preferably 45 to 75°C.
[0061] According to another embodiment of the present invention, the drying time may be 1 to 12 hours, preferably 2 to 10 hours, and more preferably 3 to 8 hours.
[0062] In the present invention, drying can be achieved by any drying method or drying apparatus known in the art, and is not particularly limited here. For example, but not limited to, vacuum drying can be used.
[0063] Reasonable concentration and drying conditions, in addition to eliminating moisture, are more conducive to the formation of the product and maintaining a stable state, which is beneficial to subsequent nitrogen doping.
[0064] Heat treatment steps
[0065] The dried product is heat-treated under protective gas at 200-1200 DEG C to obtain a nitrogen-doped carbon carrier.
[0066] According to one embodiment of the present invention, the temperature of the heat treatment may be 200 to 1200°C, preferably 300 to 1000°C, and more preferably 350 to 800°C.
[0067] According to another embodiment of the present invention, the heat treatment time may be 0.5 to 10 hours, preferably 1 to 8 hours, and more preferably 1 to 5 hours.
[0068] According to one embodiment of the present invention, the heating rate of the heat treatment may be 2 to 10° C. / min, preferably 3 to 9° C. / min, and more preferably 4 to 8° C. / min.
[0069] In the present invention, the protective gas can be selected from at least one of nitrogen (N2) and an inert gas, the inert gas including helium (He), neon (Ne), argon (Ar), krypton (Kr), and xenon (Xe); preferably, the protective gas is selected from at least one of nitrogen, helium, neon, and argon; more preferably, the protective gas is selected from at least one of nitrogen, helium, and argon.
[0070] In the present invention, the heat treatment can be performed in any type of high-temperature heat treatment furnace known in the art, and is not particularly limited here, such as but not limited to a high-temperature sintering furnace or a high-temperature tubular furnace.
[0071] Limiting the heat treatment conditions to the above range can ensure that the carbon support forms a suitable pore structure and is conducive to the formation of nitrogen doping.
[0072] Mixing steps of precious metals and rare earth elements
[0073] The nitrogen-doped carbon carrier is mixed with a solution of a salt of a noble metal and a solution of a salt of a rare earth element under the conditions of neutralization of C2-C5 alkanediol and protective gas to obtain a mixed solution.
[0074] According to one embodiment of the present invention, the rare earth element can be selected from at least one of neodymium (Nd), lanthanum (La), cerium (Ce), praseodymium (Pr), terbium (Tb), and dysprosium (Dy), preferably at least one of neodymium, praseodymium, lanthanum, and cerium, and more preferably at least one of neodymium, lanthanum, and cerium.
[0075] According to one embodiment of the present invention, the salt of the rare earth element may be selected from at least one of the halides of the rare earth element, preferably at least one of the chlorides of the rare earth element and the bromides of the rare earth element, more preferably the chlorides of the rare earth element.
[0076] According to one embodiment of the present invention, the precious metal can be selected from at least one of platinum (Pt), rhodium (Rh), palladium (Pd), and iridium (Ir), preferably at least one of platinum, rhodium, and palladium, and more preferably at least one of platinum and palladium.
[0077] According to one embodiment of the present invention, the salt of the noble metal may be selected from at least one of a halogenated noble metal acid and a halogenated noble metal acid salt of an alkali metal, preferably at least one of a chlorinated noble metal acid, a brominated noble metal acid, a chlorinated noble metal acid salt of an alkali metal, and a brominated noble metal acid salt of an alkali metal, more preferably at least one of a chlorinated noble metal acid and a chlorinated noble metal acid salt of an alkali metal. The alkali metal is preferably at least one of sodium and potassium.
[0078] According to an embodiment of the present invention, the mass ratio of the salt of rare earth elements to the salt of noble metals can be 1:1 to 10, preferably 1:2 to 8, and more preferably 1:2 to 6.
[0079] A reasonable ratio of noble metals to rare earth elements is conducive to the uniform distribution of alloy nanoparticles of noble metals and rare earth elements, and is more conducive to improving the performance of the nitrogen-doped alloy catalyst.
[0080] According to an embodiment of the present invention, under the condition of protective gas, the pH value of the mixed solution is adjusted to 8 to 12, preferably 9 to 11, and more preferably 9 to 10.
[0081] According to a specific embodiment of the present invention, the pH value of the mixed solution can be adjusted using an alkylene glycol solution of alkali metal hydroxide having 2 to 5 carbon atoms.
[0082] In the present invention, the alkali metal hydroxide can be selected from at least one of LiOH, NaOH, and KOH, preferably at least one of NaOH and KOH, and more preferably NaOH or KOH.
[0083] According to an embodiment of the present invention, the solvents used in the solution of the salt of noble metals and the solution of the salt of rare earth elements are respectively alkylene glycols having 2 to 5 carbon atoms.
[0084] In the present invention, the alkylene glycol having 2 to 5 carbon atoms can be an alkylene glycol having 2 to 4 carbon atoms, preferably at least one of ethylene glycol, 1,2-propanediol, 1,3-propanediol, and 1,4-butanediol, and more preferably at least one of ethylene glycol, 1,2-propanediol, and 1,4-butanediol.
[0085] The concentration of the alkylene glycol solution of alkali metal hydroxide can be any concentration and is not particularly limited herein.
[0086] A reasonable pH value of the mixed solution is conducive to the reduction of metal ions and the formation of metal nanoparticles. At the same time, a reasonable pH value can also prevent the aggregation and inactivation of metal particles, which is beneficial to maintaining the stability of the nitrogen-doped alloy catalyst.
[0087] According to a specific embodiment of the present invention, before and after adjusting the pH value of the mixed solution, the mixing of the mixed solution can be promoted by stirring under the condition of protective gas. The stirring method can use any stirring method known in the art and is not particularly limited herein. The stirring time is based on being stirred evenly and is not particularly limited herein. For example, but not limited to, it can be 5 to 90 min, preferably 10 to 80 min, and more preferably 10 to 60 min.
[0088] The protective gas can be selected from at least one of nitrogen (N2) and an inert gas, the inert gas including helium (He), neon (Ne), argon (Ar), krypton (Kr), and xenon (Xe); preferably, the protective gas is selected from at least one of nitrogen, helium, neon, and argon; more preferably, the protective gas is selected from at least one of nitrogen, helium, and argon.
[0089] Reduction reaction steps
[0090] The mixed solution after adjusting the pH value is mixed with the solution of the reducing agent under the conditions of protective gas and 40-120 DEG C and reacted to prepare the nitrogen-doped alloy catalyst.
[0091] According to one embodiment of the present invention, the reaction temperature may be 40 to 120°C, preferably 50 to 110°C, and more preferably 60 to 100°C.
[0092] According to one embodiment of the present invention, the reaction time may be 0.5 to 12 h, preferably 1 to 10 h, and more preferably 2 to 8 h.
[0093] According to one embodiment of the present invention, the reducing agent can be selected from at least one of alkali metal borohydrides, sodium D-isoascorbate, catechol, ferrous sulfate, and stannous chloride, preferably at least one of alkali metal borohydrides, ferrous sulfate, and stannous chloride, more preferably alkali metal borohydrides.
[0094] The alkali metal may be selected from at least one of lithium, sodium and potassium, preferably at least one of sodium and potassium, more preferably sodium or potassium.
[0095] According to one embodiment of the present invention, the solvent used in the solution of the reducing agent is C2-C5 alkanediol.
[0096] The C2-C5 alkanediol may be a C2-C4 alkanediol, preferably at least one of ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and 1,4-butanediol, and more preferably at least one of ethylene glycol, 1,2-propylene glycol, and 1,4-butanediol.
[0097] According to one embodiment of the present invention, the mass of the reducing agent may be 1 to 10 times, preferably 2 to 9 times, and more preferably 2 to 5 times the mass of the salt of the precious metal.
[0098] Reasonable reducing agents and reducing conditions are conducive to reducing precious metal ions and rare earth element ions to metal elements, and are more conducive to the formation of metal nanoparticles that serve as catalyst active centers.
[0099] The present invention may also include the steps of cooling, filtering, washing and drying the prepared nitrogen-doped alloy catalyst.
[0100] In the present invention, cooling can be achieved by any method known in the art, and is not particularly limited herein, such as natural cooling or air cooling.
[0101] The washing detergent can be selected from at least one of water and C1-C5 alkyl alcohols, preferably water and at least one of C1-C3 alkyl alcohols, more preferably water and at least one of C1-C3 n-alkyl alcohols, most preferably at least one of deionized water, methanol, ethanol and n-propanol.
[0102] In the present invention, the C1-C5 alkyl alcohol may include but is not limited to methanol, ethanol, propanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, n-pentanol, isopentanol, sec-pentanol, neopentyl alcohol and the like.
[0103] The washing times in the present invention may be 1 to 6 times, preferably 2 to 5 times, and more preferably 3 to 5 times. The washing method may be washing with one detergent or washing with different detergents at different washing times, which is not particularly limited here.
[0104] The filtration may be performed by any filtration method known in the art, without particular limitation, and may be gravity filtration, pressure filtration, centrifugal filtration, vacuum filtration, etc. Various filtration methods may be performed using equipment known in the art.
[0105] According to one embodiment of the present invention, the drying temperature may be 40 to 100°C, preferably 45 to 90°C, and more preferably 50 to 85°C.
[0106] According to another embodiment of the present invention, the drying time may be 6 to 48 hours, preferably 12 to 42 hours, and more preferably 15 to 40 hours.
[0107] <Nitrogen-doped alloy catalyst>
[0108] The present invention also provides a nitrogen-doped alloy catalyst obtained by the method.
[0109] According to one embodiment of the present invention, the pore diameter of the nitrogen-doped alloy catalyst of the present invention may be at least 9 nm, preferably at least 10 nm, and more preferably 10 to 15 nm.
[0110] According to one embodiment of the present invention, the pore volume of the nitrogen-doped alloy catalyst of the present invention may be at most 0.37 cm 3 ·g -1 , preferably at most 0.368 cm 3 ·g -1 , more preferably 0.35 to 0.368 cm 3 ·g -1 .
[0111] According to one embodiment of the present invention, the noble metal loading of the nitrogen-doped alloy catalyst of the present invention may be at least 11 μg·cm -2 , preferably at least 12 μg·cm -2 , more preferably 12 to 15 μg·cm -2 .
[0112] The nitrogen-doped alloy catalyst of the present invention is composed of alloy nanoparticles of noble metals and rare earth elements uniformly distributed on a nitrogen-doped carbon carrier. The carbon carrier of the nitrogen-doped alloy catalyst has a suitable pore structure, which can ensure that the catalyst has abundant catalytic active sites. The uniform distribution of the alloy nanoparticles of noble metals and rare earth elements and the synergistic effect of the nitrogen-doped carbon carrier can significantly improve the catalytic activity of the catalyst.
[0113] <Purpose>
[0114] The present invention also provides use of the nitrogen-doped alloy catalyst in a proton exchange membrane fuel cell.
[0115] In the present invention, the nitrogen-doped alloy catalyst is used as a cathode catalyst in a proton exchange membrane fuel cell, and the half-wave potential in the oxygen reduction reaction can be at least 0.91V, preferably at least 0.915V, and more preferably 0.915-0.93V; the Tafel slope can be at most 40mV·dec -1 , preferably at most 38 mV·dec -1 , more preferably 30 to 38 mV·dec -1 .
[0116] The nitrogen-doped alloy catalyst of the present invention has a high half-wave potential and a low Tafel slope, has excellent catalytic activity and catalytic kinetic performance in oxygen reduction reaction, and is particularly suitable for use as a cathode in a proton exchange membrane fuel cell.
[0117] <Test method>
[0118] TEM measurement was carried out using a Japanese JEOL JEM-F200 field emission transmission electron microscope.
[0119] BET determination: carried out using Beckman Coulter SA3100 instrument from the United States.
[0120] PXRD (powder X-ray diffraction) measurement: carried out using XPert Pro MPD instrument from PANalytical, the Netherlands.
[0121] Nitrogen adsorption and desorption test
[0122] In accordance with GB / T 19587-2017.
[0123] Platinum loading determination
[0124] The test was carried out using the Swiss ADVANT'XP+ Thermo Fisher X-ray fluorescence spectrometer. By detecting the energy and intensity of these fluorescence signals, the content of platinum in the sample can be determined.
[0125] Linear Sweep Voltammetry (LSV) with a Rotating Ring Disk Electrode
[0126] 5 mg of Pt-Nd@HCN-400, Pt-Nd@HC-400 and commercial catalyst JM (Johnson Matthey) Pt / C (referred to as Pt / C) were added to 1 mL of anhydrous ethanol and ultrasonically stirred for 5 min. Then, 120 μL of 5% Nafion solution was added to the solution and ultrasonically stirred for another 5 min to prepare three catalyst solutions with a concentration of 5 mg / mL.
[0127] 20 μL of each of the three catalyst solutions was taken and dropped onto the platinum carbon electrode of the rotating ring disk electrode to prepare the working electrode. The working electrode was prepared in a 0.1 M HClO4 solution at 1600 rpm and 10 mV·s -1 The experiment was carried out at a scan rate of 1.5 and the LSV curve was recorded. 0.1M HClO4 solution was saturated in both N2 and O2 environments.
[0128] The rotating ring disk electrode adopts the AFMSRCE type produced by PINE Company of the United States.
[0129] <Ingredients>
[0130] The other raw materials in the following examples are all commercially available products unless otherwise specified.
[0131] The purity of the raw materials used in the present invention is at least industrial purity (99.9 wt%).
[0132] The carbon black used in the present invention is Vulcan XC-72 carbon powder.
[0133] The Pt / C catalyst used in the present invention is JM (Johnson Matthey) Pt / C catalyst.
[0134] Raw material preparation example 1
[0135] Weigh 1 g of H2PtCl6·6H2O and dissolve it in 50 mL of ethylene glycol to prepare an ethylene glycol solution of chloroplatinic acid with a concentration of 0.039 M.
[0136] Weigh 2 g of NdCl3·6H2O and dissolve it in 250 mL of ethylene glycol to prepare an ethylene glycol solution of neodymium chloride with a concentration of 0.022 M.
[0137] 5.6 g of KOH was weighed and dissolved in 100 mL of ethylene glycol to prepare an ethylene glycol solution of potassium hydroxide with a concentration of 1 M.
[0138] Weigh 7.57 g of NaBH4 and dissolve it in 100 mL of ethylene glycol to prepare a 2 M sodium borohydride ethylene glycol solution.
[0139] Raw material preparation example 2
[0140] Weigh 2 g of SmCl3·6H2O and dissolve it in 250 mL of ethylene glycol to prepare an ethylene glycol solution of samarium chloride with a concentration of 0.022 M.
[0141] Example 1
[0142] Dissolve 150 mg of urea in 100 mL of ethylene glycol and stir well to obtain an ethylene glycol solution of urea. Add 400 mg of carbon black to the obtained ethylene glycol solution of urea and treat it with ultrasound for 30 minutes to obtain a mixed solution. Rotary evaporate the mixed solution at 70°C for 12 hours and then vacuum dry it at 50°C for 4 hours. Put the dried product into a tubular furnace, heat it to 400°C at a rate of 5°C / min in a nitrogen atmosphere, heat treat it at 400°C for 1 hour, and naturally cool it to room temperature (25°C, the same below) to obtain a nitrogen-doped carbon carrier (referred to as HCN-400).
[0143] 80 mg of HCN-400 was placed in 40 mL of ethylene glycol and ultrasonically treated for 30 min to prepare an ethylene glycol solution of HCN-400. Then, 2.415 mL of the ethylene glycol solution of chloroplatinic acid and 1.4 mL of the ethylene glycol solution of neodymium chloride prepared above were added dropwise to the ethylene glycol solution of HCN-400 under an argon atmosphere. After the addition was completed, the solution was stirred for 30 min to mix the solution evenly to obtain a mixed solution. The ethylene glycol solution of KOH prepared above was added dropwise to the mixed solution, and the pH value of the mixed solution was adjusted to 9. Then, the mixed solution was stirred for 30 min under an argon atmosphere. After stirring, the mixed solution was heated to 80 ° C, and 1.5 mL of the ethylene glycol solution of sodium borohydride prepared above was added dropwise at 80 ° C, and the reaction was allowed to react for 3 h. After the reaction was completed, it was naturally cooled to room temperature, the reaction product was filtered, and the reaction product was washed with ethanol twice and with water once. The washed reaction product was dried at 60° C. for 24 h to obtain a nitrogen-doped alloy catalyst (denoted as Pt-Nd@HCN-400).
[0144] Comparative Example 1
[0145] The only difference from Example 1 is that the ethylene glycol solution of samarium chloride prepared above is used instead of the ethylene glycol solution of neodymium chloride to prepare a nitrogen-doped alloy catalyst (denoted as Pt-Sm@HC-400).
[0146] Comparative Example 2
[0147] The only difference from Example 1 is that urea is not added, the obtained carbon support is recorded as HC-400, and the obtained alloy catalyst is recorded as Pt-Nd@HC-400.
[0148] Experimental Example 1
[0149] The TEM images of the catalysts obtained in Example 1, Comparative Example 1 and Comparative Example 2 are shown in FIG. Figure 1 , Figure 2 and Figure 3 .
[0150] Depend on Figure 1 It can be seen that the Pt-Nd alloy particles in Pt-Nd@HCN-400 are evenly distributed, and no large amount of Pt-Nd alloy particles are found on nitrogen-doped carbon, and only slight aggregation is observed in some areas. The average particle size of the Pt-Nd alloy particles is 3.07nm.
[0151] Depend on Figure 2 It can be seen that there are many platinum agglomerates on the surface of Pt-Sm@HCN-400, which will damage the electron transport and affect the catalytic activity of the catalyst.
[0152] Depend on Figure 3 It can be seen that the particles of Pt-Nd@HC-400 without the addition of nitrogen precursor have agglomeration, the morphology is irregular, and the degree of platinum loading is weakened at the edge. The average particle size of the Pt-Nd alloy particles is 4.54nm.
[0153] The BET calculation results of the carbon carriers obtained in Example 1 and Comparative Example 2 are shown in Figure 4 .Depend on Figure 4 It can be seen that the pore size of Pt-Nd@HC-400 is 8.821nm, and the pore size of Pt-Nd@HCN-400 is 10.319nm, which provides a good attachment site for Pt-Nd alloy particles and lays a foundation for the catalyst to have excellent catalytic effect. The pore volumes of Pt-Nd@HC-400 and Pt-Nd@HCN-400 are 0.386cm 3 ·g -1 and 0.366cm 3 ·g -1 The pore volume of Pt-Nd@HCN-400 is small, which is due to the blocking of some microporous channels by nitrogen atom groups.
[0154] Figure 5The nitrogen absorption and denitrification curves of Pt-Nd@HCN-400 and Pt-Nd@HC-400 are shown as type III and type IV curves, respectively, indicating that both are mesoporous structures. The advantage of the mesoporous structure is that it can reduce the mass transfer resistance, thereby improving the redox efficiency. Figure 4 It can be seen that the pore size of the nitrogen-doped carbon carrier HCN-400 is 10.319nm, while the pore size of the non-nitrogen-doped carbon carrier HC-400 is 8.821nm. Since nitrogen atoms are larger than carbon atoms, the pores of HCN-400 are significantly larger than those of HC-400. In addition, the addition of nitrogen increases the spacing between carbon layers, resulting in a loose arrangement of the carbon skeleton, which ultimately leads to an increase in the overall pore size. The modification effect of nitrogen on carbon is further clarified. The specific surface area of the nitrogen-doped carbon carrier is slightly reduced, which is due to the blocking of some micropores by larger nitrogen atom groups. The above analysis results show that the nitrogen-doped carbon carrier exhibits a better pore size distribution compared with the carbon carrier that is not nitrogen-doped.
[0155] Experimental Example 2
[0156] In order to clarify the crystal structure of the catalyst, powder X-ray diffraction (PXRD) analysis was performed on the Pt-Nd@HCN-400 prepared in Example 1 and the Pt-Nd@HC-400 prepared in Comparative Example 2. Figure 6 The PXRD patterns of Pt-Nd@HCN-400 and Pt-Nd@HC400 are shown in Figure 2. We compared the results with the PDF cards of Pt (PDF#87-0647) and Nd (PDF#39-0914). The results show that the diffraction peaks of the two catalysts are similar, and the (111), (200) and (220) peaks of the face-centered cubic Pt crystal are located near 2θ=39.9°, 2θ=46.4° and 2θ=67.7°, respectively. The Nd diffraction peaks of Pt-Nd@HCN-400 show different degrees of peak shifts. This indicates that the Pt ions in the catalyst are successfully reduced to Pt element. The two catalysts show the same XRD peaks. The peak shifts of both catalysts occur between the standard peaks of pure Nd and pure Pt, which indicates that Nd atoms and Pt atoms undergo metal-metal interactions to form alloys.
[0157] Experimental Example 3
[0158] The commercial electrode Pt / C was selected as a control, and the platinum loadings in Pt-Nd@HCN-400 and Pt / C prepared in Example 1 were measured respectively. The platinum loading of Pt-Nd@HCN-400 was 12 μg cm -2 , the platinum loading of Pt / C is 10 μg cm -2 .
[0159] Experimental Example 4
[0160] In order to evaluate the ORR (oxygen reduction reaction) performance of the nitrogen-doped alloy catalyst of the present invention, a three-electrode system was used, and the Pt-Nd@HCN-400 prepared in Example 1, the Pt-Nd@HC400 prepared in Comparative Example 2, and the commercial electrode Pt / C were tested by rotating ring disk electrode using linear sweep voltammetry (LSV). The results are shown in FIG. Figures 7 to 9 shown.
[0161] The LSV curve shows that the half-wave potentials of Pt / C, Pt-Nd@HC-400 and Pt-Nd@HCN-400 are 0.893V, 0.902V and 0.918V, respectively. Among them, Pt-Nd@HCN-400 exhibits the most outstanding electrochemical catalytic performance, and its LSV curve is not only smoother and more stable, but also has a larger value of the half-wave potential. The inventors believe that this significant activity improvement is mainly attributed to the introduction of nitrogen, which triggers the redistribution of charge, effectively reduces the ORR potential, and changes the electronic structure of O, thereby weakening the OO bond, greatly promoting the ORR process on the electrode. As can be seen from the figure, relative to Pt / C, the LSV curve of Pt-Nd@HCN-400 has a high half-wave potential and starting potential, further illustrating that the nitrogen-doped alloy catalyst of the present invention has a very strong ORR activity.
[0162] The Tafel slope is calculated based on the LSV curve data. The results are as follows: Fig.10 As shown. Fig.10 It can be seen that the Tafel slopes of Pt / C, Pt-Nd@HC-400 and Pt-Nd@HCN-400 are 50.74 mv·dec respectively. -1 、54.26mv·dec -1 and 36.61mv·dec -1 , indicating that the reaction kinetics of the nitrogen-doped alloy catalyst of the present invention is the best.
[0163] From the results after 3600s in the LSV curve diagram, it can be seen that the current density curve (red) after 3600 seconds is very close to the curve shape and position of the initial state (black), which shows that the current density of the nitrogen-doped alloy catalyst of the present invention remains relatively stable after long-term testing. The current density curve of the nitrogen-doped alloy catalyst of the present invention after 3600 seconds is compared with the initial curve, and the overall current density has decreased, but the decline is very small, which means that the performance of the catalyst has not significantly decreased after long-term use. Since the current density is directly related to the activity of the catalyst, therefore, the current density curve after 3600 seconds is highly overlapped with the initial curve, indicating that the catalyst can still maintain a high catalytic activity after long-term testing and has good durability.
[0164] The present invention is not limited to the above-mentioned embodiments. Without departing from the essential content of the present invention, any deformation, improvement and substitution that can be conceived by those skilled in the art shall fall within the scope of the present invention.
Claims
1. A method for preparing a nitrogen-doped alloy catalyst, comprising the following steps: 1) dissolving a nitrogen precursor in a C2-C5 alkanediol to prepare a nitrogen precursor solution; Adding the carbon carrier to the nitrogen precursor solution and mixing them to obtain a mixed solution; wherein the mass ratio of the nitrogen precursor to the carbon carrier is 1:1 to 10; 2) concentrating the mixed solution obtained in step 1) to obtain a concentrated product; drying the concentrated product to obtain a dried product; 3) heat treating the dried product obtained in step 2) under protective gas at 200-1200° C. to obtain a nitrogen-doped carbon support; 4) mixing the nitrogen-doped carbon support obtained in step 3) with a solution of a noble metal salt and a solution of a rare earth element salt under the conditions of neutralization of C2-C5 alkanediol and protective gas to obtain a mixed solution; and adjusting the pH value of the mixed solution to 8-12; wherein the mass ratio of the salt of the rare earth element to the salt of the noble metal is 1:1-10; and the rare earth element is selected from at least one of neodymium, lanthanum, cerium, praseodymium, terbium, and dysprosium; 5) The mixed solution after adjusting the pH value in step 4) is mixed with a solution of a reducing agent under protective gas and 40-120° C. to react to obtain a nitrogen-doped alloy catalyst.
2. The preparation method according to claim 1, characterized in that: The solvents used in the solution of the salt of the precious metal, the solution of the salt of the rare earth element, and the solution of the reducing agent are respectively C2-C5 alkanediols; The C2-C5 alkanediol is a C2-C4 alkanediol.
3. The preparation method according to claim 1, characterized in that: In step 1), the nitrogen precursor is selected from at least one of urea, ethylenediamine, benzylamine, melamine, pyrazine, polyacrylonitrile, and polypyrrole; and the carbon carrier is selected from at least one of carbon black, carbon nanotubes, mesoporous carbon, and graphene.
4. The preparation method according to claim 1, characterized in that: In step 2), the concentration temperature is 50-100° C., and the concentration time is 6-24 hours; the drying temperature is 30-90° C., and the drying time is 1-12 hours.
5. The preparation method according to claim 1, characterized in that: In step 4), the noble metal is selected from at least one of platinum, rhodium, palladium and iridium; the salt of the noble metal is selected from at least one of a halogenated noble metal acid and a halogenated noble metal acid salt of an alkali metal; In step 4), the salt of the rare earth element is selected from at least one of the halides of the rare earth element.
6. The preparation method according to claim 1, characterized in that: In step 4), a C2-C5 alkanediol solution of an alkali metal hydroxide is used to adjust the pH value of the mixed solution.
7. The preparation method according to claim 1, characterized in that: In step 5), the reducing agent is selected from at least one of alkali metal borohydride, sodium D-isoascorbate, catechol, ferrous sulfate, and stannous chloride.
8. The preparation method according to claim 1, characterized in that: The protective gas is selected from at least one of nitrogen and inert gas.
9. A nitrogen-doped alloy catalyst prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The nitrogen-doped alloy catalyst has a pore size of at least 9 nm and a pore volume of at most 0.37 cm 3 ·g -1 , the precious metal loading is at least 11 μg cm -2 .
10. Use of the nitrogen-doped alloy catalyst according to claim 9 in a proton exchange membrane fuel cell, characterized in that: The nitrogen-doped alloy catalyst as a cathode catalyst has a half-wave potential of at least 0.91 V and a Tafel slope of at most 40 mV·dec in an oxygen reduction reaction. -1 .
Citation Information
Patent Citations
Rare earth element doped carbon nitride loaded noble metal electrocatalyst as well as preparation method and application thereof
CN118825307A
Cited By
Rare earth doped stable carbon carrier-based low-iridium-loading corrosion-resistant anode catalyst and preparation method and application thereof
CN121137679A